Perioperative renal transplantation management in small children using adult‐sized living or deceased donor kidneys: A single‐center experience. (22nd July 2019) - Lee, Eliza; Ramos-Gonzalez, Gabriel; Staffa, Steven J.; Rodig, Nancy; Vakili, Khashayar; Kim, Heung Bae
Abstract: Kidney transplantation remains the treatment of choice for children with ESRD. Optimal perioperative management is critical in small recipients of ASK to assure adequate graft perfusion. We present a single‐center experience outlining management for patients weighing <20 kg who underwent primary renal transplantation with ASKs between 2007 and 2016. Sixty‐three patients met study criteria and underwent 34 living‐related, six living‐unrelated, and 23 deceased donor kidney transplants. Median age and weight at transplant were 25 months (IQR 18‐37 months; range 11 months‐6 years) and 11.0 kg (IQR 9.2‐14.5 kg; range 7.1‐19.5 kg). Eighty‐nine percent of patients required vasoactive agents intra‐operatively, with twenty patients requiring prolonged vasoactive agents post‐operatively. Intra‐operatively, patients received 51.9 mL/kg of crystalloid, 27.3 mL/kg of 5% albumin, and 13.6 mL/kg of packed red blood cells. Most (93.7%) patients were extubated on POD#0. Weights peaked on post‐operative days three through five. Over a median follow‐up of 49 months (IQR 31‐86 months; range 0‐130 months), four grafts were lost, two due to thrombosis and two secondary to chronic rejection. There was one patient death six months post‐transplant due to causes unrelated to transplantation. Graft survival at 1, 5, and 10 years was 98.4%, 96.6%, and 84.2%, respectively. Of surviving allografts, the median 1, 5, and 10 years post‐transplant eGFR was 122.9, 90.0, and 59.2 mL/min/1.73 m 2 as determined by the 2009 Schwartz formula. Renal transplantation in small children using ASKs requires meticulous perioperative management including adequate fluid resuscitation and judicious use of pressors to assure adequate graft perfusion. The use of ASKs from living or deceased donors results in satisfactory short and long‐term outcomes.